2010
DOI: 10.2460/ajvr.71.12.1432
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of 5-hydroxytryptamine 4 receptors in smooth muscle preparations from the duodenum, ileum, and pelvic flexure of horses without gastrointestinal tract disease

Abstract: In horses, 5-HT4 receptors on smooth muscle cells appear to be involved in the contractile response of the intestinal tract to 5-hydroxytryptamine. Results suggest that tegaserod may be useful for treatment of reduced gastrointestinal tract motility in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The present study provides solid evidence of 5‐HT 4 ‐IR in the MP and SMP neurons of horse intestine. Despite some functional investigations carried out on horse small and large intestine indicated the presence of 5‐HT 4 in the ENS of this animal model, the only immunohistochemical study carried out on horse ENS failed to detect 5‐HT 4 in enteric neurons, but confirmed the presence of this serotonergic receptor on muscular layers . Furthermore, a recent study by Delesalle et al .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present study provides solid evidence of 5‐HT 4 ‐IR in the MP and SMP neurons of horse intestine. Despite some functional investigations carried out on horse small and large intestine indicated the presence of 5‐HT 4 in the ENS of this animal model, the only immunohistochemical study carried out on horse ENS failed to detect 5‐HT 4 in enteric neurons, but confirmed the presence of this serotonergic receptor on muscular layers . Furthermore, a recent study by Delesalle et al .…”
Section: Discussionmentioning
confidence: 80%
“…Despite some functional investigations carried out on horse small and large intestine indicated the presence of 5-HT 4 in the ENS of this animal model, [23][24][25][26][27][28][29][30][31][32][33] the only immunohistochemical study carried out on horse ENS failed to detect 5-HT 4 in enteric neurons, but confirmed the presence of this serotonergic receptor on muscular layers. 31 Furthermore, a recent study by Delesalle et al 39 receptor were already observed in the rat spinal ganglia. 22 As 5-HT 4 -IR was co-expressed by extrinsic SP-IR sensory fibers of aganglionotic LWFS foals, it is plausible that this receptor might play a role in nociception.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…5-HT 4 receptors, on the other hand, are G protein-coupled receptors that stimulate cAMP production (30). 5-HT 4 receptors are localized in the enteric neurons (35), smooth muscles (32), and epithelial cells including the EC cells (15). Effects of 5-HT mediated secretion in Ussing chamber involve activation of both neuronal and nonneuronal 5-HT 3 and 5-HT 4 receptors (6,26,31).…”
mentioning
confidence: 99%
“…5-HT4 receptors, linked to adenylyl cyclase, act via generation of cAMP. None of the 4 in vitro studies on 5-HT in horses provided evidence for neuronal 5-HT4 receptors, but none used the protocol as described in human studies [1][2][3][4].…”
Section: Ethical Animal Researchmentioning
confidence: 99%